2006
DOI: 10.1002/bjs.5467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaginal delivery on long-term pouch function

Abstract: Women who had RP and vaginal delivery with a high risk of obstetric injury had impaired continence with ageing and longer follow-up. Patients with RP should be informed about the considerable risk of vaginal delivery on long-term ileal pouch function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…The review of gastrointestinal or pouch complications included eight of the 14 studies [4,7,9,10,12,14,16,18]. Of the six studies which were excluded, three did not report complications [13,15,17] and three included women reported in more recent publications [7,8,11]. Overall, the rate of complications in 283 pregnancies following IPAA was 12.7% (36/ 283; Table II).…”
Section: Review Of the Literaturementioning
confidence: 94%
See 3 more Smart Citations
“…The review of gastrointestinal or pouch complications included eight of the 14 studies [4,7,9,10,12,14,16,18]. Of the six studies which were excluded, three did not report complications [13,15,17] and three included women reported in more recent publications [7,8,11]. Overall, the rate of complications in 283 pregnancies following IPAA was 12.7% (36/ 283; Table II).…”
Section: Review Of the Literaturementioning
confidence: 94%
“…The remainder used proprietary questionnaires. Some studies included all pregnancies after IPAA while others included only the first pregnancy after IPAA [8], most recent pregnancy [10], or did not differentiate between pregnancies before and after IPAA [17]. A cohort of women who became pregnant after appendectomy was used as controls in one study [18].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Two studies including patients undergoing vaginal delivery with similar follow-up periods (7.2 yr versus 8 yr) found contrasting results. One study (n ¼ 52) reported a high risk of obstetric injury and impaired continence, 91 whereas the other study (n ¼ 85) found the lack of adverse impact on pouch functions. 92 Additionally, other studies that compared vaginal delivery with C-section found no difference in pouch functional outcomes, despite one study having higher incidence of sphincter dysfunction in patients who underwent vaginal delivery.…”
Section: Impact Of Childbirth On Ipaamentioning
confidence: 98%